The radiology impact of healthcare errors during shift work. Issue 3 (August 2020) - Elliott, J.; Williamson, K.
Abstract: Objectives: What are the risks of error as a result of out-of-hours work in health care that could be attributed to Shift Work Disorder; and what safety implications would this have for radiographers working with ionising radiation? To conduct a literature search of existing studies of Shift Work Disorder. To critically appraise appropriate studies for research rigour. To synthesize and discuss findings in the selected research articles. To investigate the impact of the results in relation to medical imaging and safety. Key findings: A systematic review of the literature was planned and executed to meet the above objectives. Narrative synthesis was used to describe the heterogeneous findings of the studies appraised. Conclusion: Four of the five studies selected after critical appraisal suggested a positive correlation of error with increased mental and physical fatigue as a result of shift work or rapid shift rotation. No studies directly investigated medical imaging professionals. Implication for practice: Considerations need to be made when optimising shift work for healthcare professionals so as to avoid Shift Work Disorder and consequential error; particularly in the context of ionising radiation. Research into environmental and lifestyle support should be pursued to study its effect as prevention or management. Further direct study with radiographers is recommended.